Knowledge Sharing Process on Sustainable Public Service Program Innovation: a case study in Surakarta City - Sutama, I Made (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge Sharing (KS) is an essential component in Knowledge Management (KM), which is the primary driver in creating sustainable innovation. Five-yearly leadership succession is always followed by massive mutations so that both phenomena have become threats to the sustainability of public service innovations. This qualitative research will explore on: How does the process of innovation program knowledge sharing occur concerning the sustainability of public service program innovations after the succession of regional heads in the Surakarta City Government? The findings have shown that there has been knowledge sharing program innovation that occurred after succession and massive mutation, which are influenced by four variables: the role of the leaders, transformation of innovative mindset, mechanism of social interaction, and external drive. In connection with these findings, further research is recommended to deepen the study of the constructed model of the proposition on local government organizations that fail to continue their program innovations post-succession. Another quantitative research construct model is to test the level of influence of the four KS variables innovation programs in both profit and non-profit organizations.